The Decline of Pesantren: Examining Leadership, Financial Constraints, and Social Transformation - Taufikin, Taufikin; Solihuddin, Moh (LPPM Universitas Ibn Khaldun, Bogor, 2025)
Islamic boarding schools (pesantren) are central to Indonesia's Islamic education system. However, in recent decades, many pesantren have faced significant challenges, ultimately leading to their closure. This study aims to identify the key factors contributing to this phenomenon, focusing on leadership, management, financial constraints, and socio-cultural changes. The research employs a qualitative approach, utilizing case studies of several pesantren in Central Java that have ceased operations. Data were collected through interviews with pesantren administrators, Kiai descendants, alumni, and local community members. Additionally, participatory observation and document analysis were conducted to gain a comprehensive understanding of the conditions preceding the closure of these institutions. The findings indicate that the lack of leadership regeneration is one of the primary factors causing institutional instability in pesantren. Many pesantren remain overly dependent on the Kiai figure without a precise succession mechanism, challenging leadership transitions. Furthermore, unprofessional management practices, such as the absence of transparent financial record-keeping and data-driven decision-making, have exacerbated the decline of these institutions. Financial constraints also pose a serious challenge, as most pesantren rely heavily on unstable community donations without implementing a diversified funding strategy. Socio-cultural factors, including shifts in societal preferences toward formal education based on science and technology and urbanization, have further diminished parental interest in enrolling their children in pesantren. This study provides valuable insights for stakeholders in Islamic education, particularly in designing policies that support pesantren sustainability. Reforming leadership systems, implementing modern management practices, diversifying funding sources, and integrating modern skill-based curricula are strategic steps that must be taken to ensure that pesantren remain relevant and sustainable in the era of globalization.